PENGARUH TIGA DIMENSI INTANGIBILITY PADA PERCEIVED RISK (STUDI TERHADAP PENGGUNAAN INTERNET) - Budhi Haryanto; Hardiyanto , (Media Riset Bisnis & Manajemen, 2009)
This study examines the influence of the three dimension of intangibility : physical, mental, and general intangibility) on perceived risk. In the model, the influences of these variables were moderated by knowledge and involvement.Survey was conducted to collect the data. Sample consists of 170 undergraduate students in business management who was taken by simple random sampling technique. Structural Equation Model (SEM) was used to explain the relations among of these observed variables.The results indicate that the perceived risk was influenced by mental intangibility and generality, moreover knowledge and involvement are variables that were found to moderate the influences of these variables. Implications for further research are also discussed. Keywords: Intangibility, Perceived risk, Knowledge, Involvement